Pengamatan Pengelolaan Keuangan UMKM dan Entrepreneur sebagai Pendukung Bluepreneur Tourism untuk Pencapaian Sustainable Tourism - Ruswan Nurmadi; Liza Novietta; Yani Suryani; Desi Ika; Rizki Fillhayati Rambe (Jurnal Pengabdian Kepada Masyarakat Digital, 2023)
Often medium, small and micro entrepreneurs (MSMEs), including entrepreneurs whose business value is included in the MSME category, are quite satisfied only if their business can survive, and have not thought about how to develop their business or so they can excel in competing with similar industries. Good financial management according to applicable accounting standards should be able to help MSME entrepreneurs to be able to see the actual situation of their business, both expenses and income, to decide on further actions for business development. On the other hand, the Government of the Republic of Indonesia has made quite a lot of development programs for MSMEs, although due to the large number of MSMEs and the many types of MSME industries, not all of the Government's programs have been able to run well. Bluepreneur Tourism for the Achievement of Sustainable Tourism is one of the Government's programs that takes advantage of Indonesia's position as an archipelagic country and the possibility of Indonesia's tourism potential recovering after the end of the covid-19 pandemic, which is expected to boost the economy, including the trade sector at the MSME level. This community service was carried out in the Baru Ladang Bambu Village, Medan Tuntungan District.Keywords: Community Service, MSMEs, Financial Management, Bluepreneur Tourism, Sustainable Tourism